2011
DOI: 10.1002/ptr.3685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alpinumisoflavone and Abyssinone V‐4′‐Methyl Ether Derived from Erythrina lysistemon (Fabaceae) on the Genital Tract of Ovariectomized Female Wistar Rat

Abstract: Erythrina lysistemon is an African medicinal plant used as a palliative for problems in women. The crude extract of this plant was shown to exhibit estrogenic effects on the female rat reproductive tract and on cell cuture. Using classic chromatographic methods, two compounds have been isolated as major constituents of this extract: alpinumisoflavone (1) and abyssinone V-4'-methyl ether (2). To determine whether both compounds are actives principles accounting for E. lysistemon effects, we applied the classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…We have previously reported a $7-fold higher increase of epithelial height in vagina compared to uterus following administration of an ethyl-acetate extract of the stem bark of E. lysistemon, a traditional "women's remedy" [29]. We have also reported that intraperitoneal injection of alpinumisoflavone, an isoflavonoid with $4-fold higher binding affinity for ERb compared to ERa, to juvenile Wistar rats produced estrogenic effects in the vagina but not the uterus; and that abyssinone, with similar binding affinities for ERa and ERb was estrogenic in the uterus as well as the vagina [30]. The report of Mvondo et al [30] is in accordance with present findings that ERb potency-selective isoflavonoids such as daidzein and dihydroglycitein are likely to display considerably lower estrogenic activity in the uterus compared to vagina.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously reported a $7-fold higher increase of epithelial height in vagina compared to uterus following administration of an ethyl-acetate extract of the stem bark of E. lysistemon, a traditional "women's remedy" [29]. We have also reported that intraperitoneal injection of alpinumisoflavone, an isoflavonoid with $4-fold higher binding affinity for ERb compared to ERa, to juvenile Wistar rats produced estrogenic effects in the vagina but not the uterus; and that abyssinone, with similar binding affinities for ERa and ERb was estrogenic in the uterus as well as the vagina [30]. The report of Mvondo et al [30] is in accordance with present findings that ERb potency-selective isoflavonoids such as daidzein and dihydroglycitein are likely to display considerably lower estrogenic activity in the uterus compared to vagina.…”
Section: Discussionmentioning
confidence: 91%
“…Using the complete Zeiss equipment consisting of a microscope (Axioskop 40) connected to a computer where the image was transferred and analyzed with the MRGrab1.0 and Axio Vision 3.1 software, all provided by Zeiss (Hallbermoos, Germany) (15,17,18); the histomorphology of the mammary glands, as well as the uterine and vaginal epithelial heights, were assessed from 5-mm sections of paraffin-embedded tissues following hematoxylin-eosin staining.…”
Section: Histological Analysismentioning
confidence: 99%
“…Ovariectomy results in a drastic decrease in uterine weight and vagina thickness at the beginning of the treatment (18,32), and these changes worsen during the period of subchronical treatment allowing dyslipidemia and decrease in bone mineral density and biomechanical strength as seen in postmenopausal women that we named the postmenopausal-like model. The model has been used previously by different laboratories to investigate the effects of natural and synthetic products on menopausal symptoms (15,33,34).…”
Section: Fig 4 Effects Of 3-day Treatment Withmentioning
confidence: 99%
“…Some abyssionones especially abyssinone V have recently been reported to inhibit the activity of the protein tyrosine phosphatase-1B (PTP 1B), which is directly linked to type-2 diabetes and obesity therapy (Na MK et al, 2006;Kone et al, 2011) and to exhibit estrogenic properties (Mvondo et al, 2012). The anticonvulsivant and sedative property of abyssinone V-4-methyl ether has not yet been evaluated.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Abyssinone V-4' methyl ether is a prenylated flavonoid isolated from plant Erythrina droogmansiana. 50 flavonoids have been obtained during the last three decades from about 15 species of Erythrina genus (Kamat et al, 1981;Njamen et al, 2003;Kebenei et al, 2011;Mvondo et al, 2012), with prenylated flavonone, isoflavones and pterocarpans being the major non alkaloid secondary metabolites isolates so far (Mvondo et al, 2012;Wandji et al, 1994). Among these metabolites, there are abyssinones which are prenylated flavonoids isolated from Erythrina abyssinica (Kebenei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%